2017
DOI: 10.3389/fnins.2017.00430
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory-Based Rehabilitation Approach: Translational Insights from Animal Models to Early Intervention

Abstract: Multisensory processes permit combinations of several inputs, coming from different sensory systems, allowing for a coherent representation of biological events and facilitating adaptation to environment. For these reasons, their application in neurological and neuropsychological rehabilitation has been enhanced in the last decades. Recent studies on animals and human models have indicated that, on one hand multisensory integration matures gradually during post-natal life and development is closely linked to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…As regards the importance of multisensory training, one study from our group assessed the impact of a short multisensory audio-motor training on spatial abilities of blind adults 20 , demonstrating that it can improve the encoding of audio motion. However, although it has been indicated that multisensory-based training trainings should be adopted early in therapeutic care to facilitate the development of body awareness 21 , very few studies tested the possibility that a similar improvement can be obtained with visually impaired children. Also, some studies assessing the impact of multisensory training in the form of virtual reality environments on the development of spatial perception showed that such technologies combining audio and haptic features might support blind people in their anticipatory exploration and cognitive mapping of the unknown space 2225 .…”
Section: Introductionmentioning
confidence: 99%
“…As regards the importance of multisensory training, one study from our group assessed the impact of a short multisensory audio-motor training on spatial abilities of blind adults 20 , demonstrating that it can improve the encoding of audio motion. However, although it has been indicated that multisensory-based training trainings should be adopted early in therapeutic care to facilitate the development of body awareness 21 , very few studies tested the possibility that a similar improvement can be obtained with visually impaired children. Also, some studies assessing the impact of multisensory training in the form of virtual reality environments on the development of spatial perception showed that such technologies combining audio and haptic features might support blind people in their anticipatory exploration and cognitive mapping of the unknown space 2225 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several evidences have demonstrated that multisensory protocols are more effective than training protocols based on unisensory stimulus regimes due to preexisting congruencies of information coming from the different senses (Shams and Seitz, 2008). This is confirmed by studies suggesting that multisensory-integrated re-habilitation methods could be effective for children with sensorial impairment (Purpura et al, 2017). In line with this view, a very recent article has shown that hemianopia can be rehabilitated with an audio-visual training procedure based on spatiotemporal concordant stimuli, stressing the benefits of multisensory stimulation (Dakos et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…In fact, it is widely accepted that the lack of early visual experience may have a negative impact on the development of spatial abilities as well as motor skills and mobility ( Fraiberg, 1968 ; Morrongiello et al, 1995 ; Prechtl et al, 2001 ; Sonksen and Dale, 2007 ). Moreover, some studies ( Aggius-vella et al, 2017 ; Purpura et al, 2017 ; Cuppone et al, 2018 ) showed how the use of other senses may help blind and low vision children to reach developmental milestones which would otherwise be difficult to achieve, such as object permanence ( Elisa et al, 2002 ; Fazzi et al, 2011 ), which is one of the main goals of our early re-habilitation. With this work, we argue that our approach may facilitate the acquisition of the ability to adapt to environmental requests, particularly important in the context of spatial cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multisensory rehabilitation paradigm has also been shown to restore some visual responsiveness in human hemianopic populations (Bolognini et al, 2005;Dundon et al, 2015a; see also Purpura et al, 2017). However, some differences in the results have also been noted.…”
Section: Discussionmentioning
confidence: 99%